Mechanistic Modelling of Coupled UV Energy Penetration and Resin Flow Dynamics in Digital Light Processing (DLP)-Based Microfluidic Chip Printing - Xinhui Wang; Antony Seng Kai Kho; Jinghang Liu; Tianyu Mao; Michael D. Gilchrist; Nan Zhang (Micromachines)
Digital light processing (DLP) technology has emerged as a promising approach for fabricating high-precision microfluidic chips due to its exceptional resolution and rapid prototyping capabilities. However, UV energy penetration and resin flow dynamics during layer-by-layer printing introduce significant challenges for microchannel printing, particularly in controlling microchannel over-curing. In this study, a novel 3D DLP over-curing interaction model (DLP-OCIM) was developed to investigate the coupled effects of UV energy penetration and directional resin flow on the over-cured structure formation of microchannels. COMSOL Multiphysics 6.1 simulations incorporating UV light propagation, photopolymerization kinetics, and resin flow dynamics revealed that microchannel over-curing is a result of both energy infiltration through previously cured layers and periodic resin flow induced by the peeling process. Experimental validation using linear and annular microfluidic chips demonstrated that increasing layer thickness induces progressive over-curing, leading to inclined cross-sectional structures. Additionally, the microchannel geometry and size significantly influence resin flow patterns, with shorter transverse microchannels producing flatter over-cured profiles compared to their longitudinal counterparts. This study provides the first comprehensive analysis of the dynamic interplay between UV energy penetration and resin flow during DLP-based microchannel fabrication, offering valuable process insights and optimization strategies for enhancing shape fidelity and printing accuracy in high-resolution microfluidic chips.